Diversity of moral thinking - "Cooper, Neil" (Oxford, 1981)
This book argues for a radically different approach to traditional and important problems of moral philosophy. The book discusses three theses; the diversity of moralities and moral judgements, their normativesness, and their possible rationality.
Keywords: Ethics